Dynamics and modelling of bubble formation in asymmetric parallel microchannels. (November 2019) - Shen, Qiuying; Zhang, Chong; Duan, Cong; Mi, Sheng; Zhu, Chunying; Fu, Taotao; Ma, Youguang
Graphical abstract: Highlights: Stability and distribution of gas-liquid two-phase flow in asymmetric parallel microchannels are focused. The cavities in the microchannel structure degrades stability, while results in better uniformity. The effects of flow resistance and fluid distribution on uniformity are analyzed. Prediction models of the relative deviation for bubble size are proposed. Abstract: Dynamics of gas-liquid two-phase flow in parallel microchannels is the bottleneck to be solved during numbering-up. This paper focuses on the stability and distribution of gas-liquid two-phase flow in asymmetric parallel microchannels. Nitrogen and glycerol-water solutions are used as the gas and liquid phases respectively. The stability of bubble formation is better under higher flow rates of gas and liquid phases. When the flow rate ratio of gas and liquid phases is smaller, the uniformity of bubbles is better. The design of cavities in the microchannel degrades stability, while results in better uniformity. The uniformity of the bubble size is the best in the microchannel configuration with both cavities in the front and the rear. The predictive models of the relative deviation E ( L ), representing the uniformity of bubbles, are proposed according to the principle of conservation of pressure drop and the resistance relationship in the parallel microchannels.